Fast Tracking Freight: A Roadmap for Growing Economy of India - Saxena, Yogesh Kumar (Journal of Commerce and Trade, 2022)
The movement of goods across the country and beyond its borders has created economic opportunities for millions of India's citizens. Today, the logistics sector represents five percent of India's Gross Domestic Product (GDP) and employs 2.2 crore people. India handles 4.6 billion tonnes of goods each year, amounting to a total annual cost of INR 9.5 lakh crore. The present study is a review on the current freight corridor vision and mission of our Prime Minister Narendra Modi. Various junk versions are being talked in the social sphere. So, the researcher thought to work upon it and to bring out a genuine significance of the government policy of dedicated freight corridor in India. The research paper is descriptive one based upon the facts and figures broadcast by the government agencies time to time. It is a secondary data analysis done on the collection made from various reports and online available data. Classifiction-JEL: R42, L31